The evaluation of technology use in implementing innovative learning environments - Vičič Krabonja, Maja; Šverc, Magdalena (Polytechnica, 2020)
Introducing ICT to schools is increasingly present not only in teaching but also in the learning process. In the Innovative Learning Environment Supported by ICT project, the goal of introducing technology is to support the transformation of lessons in order to prepare learning opportunities in which students will acquire their knowledge and develop competencies. In doing so, teachers need knowledge and tools to assess whether ICT supported activities are appropriate for achieving the set goals and enable the transformation of lessons. In the paper, we explore three models that could help teachers making these important decisions. Based on the analysis of 68 examples of lessons plans, we propose that the R.A.T. model is the most appropriate for teachers in the ’Innovative ICT-supported learning environment’ project. The benefit of the ICT implementation in teaching and learning process should be continuously monitored and evaluated.